2015
DOI: 10.1038/srep15636
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive imaging of radiolabeled exosome-mimetic nanovesicle using 99mTc-HMPAO

Abstract: Exosomes known as nano-sized extracellular vesicles attracted recent interests due to their potential usefulness in drug delivery. Amid remarkable advances in biomedical applications of exosomes, it is crucial to understand in vivo distribution and behavior of exosomes. Here, we developed a simple method for radiolabeling of macrophage-derived exosome-mimetic nanovesicles (ENVs) with 99mTc-HMPAO under physiologic conditions and monitored in vivo distribution of 99mTc-HMPAO-ENVs using SPECT/CT in living mice. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
177
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(190 citation statements)
references
References 36 publications
12
177
1
Order By: Relevance
“…The radioactivity detected in the bladder (3% of the injected radioactivity), originates from the free Tc-HMPAO method is challenging due to the low radiochemical yield of the method at low EV concentrations 34 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The radioactivity detected in the bladder (3% of the injected radioactivity), originates from the free Tc-HMPAO method is challenging due to the low radiochemical yield of the method at low EV concentrations 34 .…”
Section: Resultsmentioning
confidence: 99%
“…34 The in vivo biodistribution of ENVs used as model system for real EVs was investigated using SPECT/CT. Although this method can be used in principle to label real EVs, the low labeling efficiency of the HMPAO method at low concentrations in the case of liposomes might hinder the successful labeling of EVs.…”
Section: Resultsmentioning
confidence: 99%
“…Although EVMs exhibit characteristics extremely similar to Exos,53, 54, 124 the actual identity of EVMs needs to be clarified by further investigation.…”
Section: High‐yield Tactics: Extracellular Vesicle‐mimetic Nanovesiclesmentioning
confidence: 99%
“…Furthermore, it has gradually been revealed that EVMs show similar properties to EVs;53, 54 therefore, the method of producing EVMs might be a much more effective way to manufacture modularized EVs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, distribution of properties of nanoparticles means that samples of nanoparticles are inhomogeneous to a certain extent. Radiolabeling procedures could affect the variability of properties of nanoparticles because simple procedures can make aggregated nanoparticles (76). Furthermore, radiolabeled nanoparticles could be slightly different from unlabeled nanoparticles because radiolabelling procedures could alter the nanoparticles to some extent.…”
Section: Issues Of In Vivo Behavior Investigated By Radionanomedicinementioning
confidence: 99%